1999
DOI: 10.1097/00006842-199911000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Risk of Sudden Cardiac Death After Acute Myocardial Infarction: Testing for the Confounding Effects of Fatigue

Abstract: Symptoms of depression and fatigue overlap in patients with MI. The trend for the cognitive-affective symptoms of depression to be associated with SCD risk, even after controlling for dyspnea/fatigue, suggests that the association between depression and mortality after AMI cannot be entirely explained as a confound of cardiac-related fatigue. The independent contribution of social participation suggests a role of both depressive symptomatology and social factors in influencing mortality risk after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 42 publications
3
107
0
8
Order By: Relevance
“…The Somatic and Cognitive factors each accounted for 9% of total explained variance, within the ranges of 6-11 % (Somatic) and 8-14% (Cognitive) reported by Ward. The finding that 9% of explained variance in BDI scores was accounted for by somatic factors unrelated to depression indicates that, as suggested by several authors [3,7,[10][11][12], measurement of depressive symptoms with the BDI does pick up some variance related to somatic experience, but not depression. The amount of potential bias due to somatic symptoms, however, was small, and measurement bias did not explain the relationship between depressive symptoms and mortality.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The Somatic and Cognitive factors each accounted for 9% of total explained variance, within the ranges of 6-11 % (Somatic) and 8-14% (Cognitive) reported by Ward. The finding that 9% of explained variance in BDI scores was accounted for by somatic factors unrelated to depression indicates that, as suggested by several authors [3,7,[10][11][12], measurement of depressive symptoms with the BDI does pick up some variance related to somatic experience, but not depression. The amount of potential bias due to somatic symptoms, however, was small, and measurement bias did not explain the relationship between depressive symptoms and mortality.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous studies have found that symptoms of depression are related to increased risk of mortality following acute myocardial infarction (AMI) after controlling for demographic and disease severity variables [1][2][3][4], although not all studies have reported a significant association [5,6]. Several recent systematic reviews or meta-analyses of the independent association between post-AMI depression and mortality have concluded that unambiguous conclusions could not be reached because of incomplete control for confounding [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Arrhythmias, such as premature ventricular contractions after myocardial infarction were associated with increased risk of sudden cardiac death in patients with depression. 31 Symptoms of depression were associated with sudden death among placebo-treated patients but not among amiodorone-treated patients. 31 Finally, depression predicted rates of defibrillation for VT/ventricular fibrillation (VF) among patients with implanted cardioverter-defibrillators.…”
Section: Résumémentioning
confidence: 97%
“…31 Symptoms of depression were associated with sudden death among placebo-treated patients but not among amiodorone-treated patients. 31 Finally, depression predicted rates of defibrillation for VT/ventricular fibrillation (VF) among patients with implanted cardioverter-defibrillators. 22 Despite the growing body of evidence that preoperative depression can increase the incidence of postoperative arrhythmia, two recently published reports in CABG patients did not support this hypothesis.…”
Section: Résumémentioning
confidence: 97%